Surface treatment for ceramic coatings / impregnated materials

Infiltrating inorganic fabrics and papers with slurry mixtures forms surface-treated prepreg composites, addressing the need for improved CMC coatings by enhancing toughness and thermal resistance, and enabling efficient production of high-temperature-resistant CMCs.

JP7612603B2Active Publication Date: 2025-01-14AXIOM MATERIALS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021560569
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-11
Filing Date
2020-04-10
Publication Date
2025-01-14
Estimated Expiration
2040-04-10

AI Technical Summary

Technical Problem

Fabric-reinforced ceramic matrix composites (CMCs) require additional coatings that necessitate time, resource, and energy-intensive processes like drying and sintering, and there is a need for improved techniques and compositions that enhance toughness, thermal resistance, and high-temperature strength.

Method used

A method involving infiltrating inorganic fabrics and papers with slurry mixtures containing oxide components and liquid media, followed by drying and sintering, to form surface-treated prepreg composites, which are then cured and sintered to create fabric-reinforced ceramic matrix composites.

Benefits of technology

This approach reduces the need for additional coating steps, enhances material properties such as toughness and thermal resistance, and allows for efficient production of CMCs suitable for high-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612603000005
    Figure 0007612603000005
  • Figure 0007612603000006
    Figure 0007612603000006
  • Figure 0007612603000007
    Figure 0007612603000007
Patent Text Reader

Abstract

The present invention relates to a surface-treated prepreg composite and a corresponding method of surface-treating inorganic fabric to form a surface-treated fabric-reinforced prepreg composite, the method including infiltrating an inorganic fabric with a first slurry mixture to form an infiltrated fabric, optionally drying the infiltrated fabric, infiltrating an inorganic paper with a second slurry mixture to form an infiltrated paper, optionally drying the infiltrated paper, and applying the infiltrated paper to at least one surface of the infiltrated fabric to form a surface-treated prepreg composite.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This PCT application claims the benefit of U.S. Provisional Application No. 62 / 832,586, filed April 11, 2019, which is incorporated herein by reference in its entirety.

[0002] FIELD OF THEINVENTION The present invention provides novel surface-treated fabric-reinforced prepreg composites, ceramic matrix composite ("CMC") materials, and methods of making such composites and materials. [Background technology]

[0003] Fabric-reinforced CMC materials are particularly suitable for structural applications in the aerospace industry due to their mechanical properties (e.g., structural flexibility or lack thereof), thermal durability, and chemical stability. A typical technique used to make fabric-reinforced CMCs involves molding a fibrous material to create a preform. The porosity of the preform is then filled with a ceramic slurry, which is then cured and / or sintered to form the CMC material.

[0004] A problem associated with such CMC materials is that they require additional coatings to be applied to their ceramic-coated surface prior to their final use. These additional coatings generally require additional drying, sintering, or other processing (e.g., painting) steps that are both time-, resource-, and energy-intensive.

[0005] Thus, there is a need for both improved techniques and corresponding ceramic slurry compositions that provide an alternative to applying additional coating layers to CMC materials. In addition to more efficient application techniques, the development of surface treatments that can impart improved toughness, heat resistance, and high temperature strength to inorganic fabric materials would provide more options in managing materials used for applications that depend on their physical properties at high temperatures. Summary of the Invention [Means for solving the problem]

[0006] One aspect of the invention provides a method of forming a surface treated fabric reinforced prepreg composite, the method including infiltrating an inorganic fabric with a first slurry mixture to form an infiltrated fabric, the slurry mixture comprising an oxide component and a liquid medium; infiltrating an inorganic paper with a second slurry mixture to form an infiltrated paper, the second slurry mixture comprising an oxide component and a liquid medium; and applying the infiltrated paper to a surface of the infiltrated fabric to form the surface treated fabric reinforced prepreg composite.

[0007] Some implementations further include drying the infiltrated fabric prior to applying the infiltrated paper to a surface of the infiltrated fabric.

[0008] Some implementations further include simultaneously drying the infiltrated fabric and the infiltrated paper.

[0009] In some implementations, the inorganic fabric comprises a plurality of fibers comprising alumina, silica, mullite, zirconia, or any combination thereof, e.g., the fibers consist essentially of alumina, silica, mullite, zirconia, or any combination thereof.

[0010] In some implementations, the inorganic fabric has a thickness of about 5 mm to about 75 mm before being infiltrated with the first slurry mixture.

[0011] In some implementations, the inorganic fabric is woven, non-woven, or any combination thereof.

[0012] In some implementations, the inorganic paper comprises alumina, silica, mullite, zirconia, or any combination thereof, for example, the inorganic paper consists essentially of alumina, silica, mullite, zirconia, or any combination thereof.

[0013] In some implementations, the inorganic paper has a thickness of about 0.1 mm to about 4.99 mm before being infiltrated with the second slurry mixture.

[0014] In some implementations, the oxide component of the first slurry mixture and / or the second slurry mixture comprises one or more oxides of aluminum, silicon, boron, zirconium, yttrium, or any combination thereof.

[0015] In some implementations, the one or more oxides of the first slurry mixture and / or the second slurry mixture are provided as particles comprising spheres, hollow spheres, fibers, whiskers, or any combination thereof.

[0016] In some implementations, the first slurry mixture and / or the second slurry mixture further comprise colloidal silica having an average particle diameter of about 1 nanometer to about 10 microns.

[0017] In some implementations, the first slurry mixture and / or the second slurry mixture further comprise colloidal alumina having an average particle diameter between about 1 nanometer and about 10 microns.

[0018] In some implementations, the liquid medium of the first slurry mixture and / or the second slurry mixture is water, alcohol, or any combination thereof. For example, the first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture comprising about 0.1% to about 40% by weight colloidal silica, about 0.1% to about 10% by weight liquid medium soluble polymer, about 40% to about 85% by weight aluminum oxide powder, and about 10% to about 60% by weight water. In another example, the first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture comprising about 15% to about 30% by weight colloidal silica, about 0.1% to about 4% by weight liquid medium soluble polymer, about 45% to about 65% by weight aluminum oxide powder, and about 20% to about 40% by weight water. In some implementations, the liquid medium soluble polymer is polyvinyl alcohol.

[0019] In other implementations, the first slurry mixture and / or the second slurry mixture is an alcohol-based slurry comprising about 0.1% to about 50% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; about 40% to about 85% by weight of aluminum oxide powder; and about 5% to about 60% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C5-C8 alcohols, or any combination thereof. For example, the first slurry mixture and / or the second slurry mixture is an alcohol-based slurry comprising about 5% to about 25% by weight of one or more organic binders, the organic binder comprising a silicone resin, a polyvinyl butyral, a polyvinyl acetate, a polylactic acid, or any combination thereof; about 45% to about 65% by weight of aluminum oxide powder; and about 30% to about 50% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, a C5-C8 alcohol, or any combination thereof.

[0020] In some implementations, the pH of the first slurry mixture and / or the second slurry mixture is adjusted to a pH of about 3 to about 5 using a protic acid.

[0021] In some implementations, the first slurry mixture and / or the second slurry mixture further comprises about 0.1% to about 2% by weight of a protonic acid, for example, the first slurry mixture and / or the second slurry mixture further comprises about 0.1% to about 1% by weight of a protonic acid.

[0022] In some implementations, the first slurry mixture and / or the second slurry mixture comprise one or more additives further comprising an inorganic polymeric material, an organic polymeric material, one or more surfactants, one or more viscosity modifiers, a glycol, a polyol, or any combination thereof.

[0023] Some implementations further include curing the fabric-reinforced prepreg composite at a pressure of about 10 psi to about 200 psi and a temperature of about 75°C to about 500°C.

[0024] Some implementations further include sintering the fabric-reinforced prepreg composite at a sintering temperature of about 700°C to about 1,400°C.

[0025] In some implementations, sintering is accomplished using a heating rate of about 1° C. / min to about 10° C. / min until the sintering temperature is achieved.

[0026] Some implementations further include blending the first slurry mixture and / or the second slurry mixture using a high shear mixer, a ball mill, an attritor, a planetary, or any combination thereof.

[0027] In some implementations, the inorganic fabric is infiltrated with a first slurry mixture heated to an infiltration temperature of about 20°C to about 150°C, and / or the inorganic paper is infiltrated with a second slurry mixture heated to an infiltration temperature of about 20°C to about 150°C.

[0028] Another aspect of the invention provides a method of forming a fabric-reinforced ceramic matrix composite article, the method including providing a prepreg composite comprising one or more layers of infiltrated fabric, the infiltrated fabric comprising an inorganic fabric infiltrated with a first slurry mixture comprising an oxide component and a liquid medium, contacting the prepreg composite with a surface of a preform, applying infiltrated paper to at least one surface of the prepreg composite to form a surface-treated prepreg composite, the infiltrated paper comprising an inorganic paper infiltrated with a second slurry mixture comprising an oxide component and a liquid medium, and sintering the surface-treated prepreg composite at a sintering temperature of about 700° C. to about 1,400° C. to form a fabric-reinforced ceramic matrix composite article.

[0029] Another aspect of the invention provides a method of forming a fabric-reinforced ceramic matrix composite article, the method including providing a prepreg composite comprising one or more layers of infiltrated fabric, the infiltrated fabric comprising an inorganic fabric infiltrated with a first slurry mixture comprising an oxide component and a liquid medium, contacting the prepreg composite with a surface of a preform, applying an infiltrated paper to at least one surface of the prepreg composite to form a surface-treated prepreg composite, the infiltrated paper comprising an inorganic paper infiltrated with a second slurry mixture comprising an oxide component and a liquid medium, curing the surface-treated prepreg composite at a pressure of about 10 psi to about 200 psi and a temperature of about 75° C. to about 500° C., and sintering the surface-treated prepreg composite at a sintering temperature of about 700° C. to about 1,400° C. to form a fabric-reinforced ceramic matrix composite article.

[0030] Another aspect of the invention provides a method of forming a fabric-reinforced ceramic matrix composite article, the method including providing a prepreg composite comprising one or more layers of infiltrated fabric, the infiltrated fabric comprising an inorganic fabric infiltrated with a first slurry mixture comprising an oxide component and a liquid medium; curing the prepreg composite at a pressure of about 10 psi to about 200 psi and a temperature of about 75° C. to about 500° C. to form a cured prepreg composite; applying an infiltrated paper to at least one surface of the cured prepreg composite to form a surface-treated prepreg composite, the infiltrated paper comprising an inorganic paper infiltrated with a second slurry mixture comprising an oxide component and a liquid medium; and sintering the surface-treated prepreg composite at a sintering temperature of about 700° C. to about 1,400° C. to form a fabric-reinforced ceramic matrix composite article.

[0031] Another aspect of the invention provides a surface treated prepreg composite comprising: an infiltrated fabric having a top layer and a bottom layer, the infiltrated fabric comprising (or consisting essentially of) fibers comprising alumina, silica, mullite, or any combination thereof, the top and bottom layers coating one or more of the fibers, each surface layer comprising about 40% to about 85% by weight (by weight of the surface layer) aluminum oxide or about 0.1% to about 40% by weight silica (by weight of the surface layer); and an infiltrated paper substantially covering and in contact with the top and / or bottom layers of the infiltrated fabric, the infiltrated paper comprising (or consisting essentially of) fibers comprising alumina, silica, mullite, or any combination thereof, the infiltrated paper being infiltrated with a slurry mixture comprising an oxide component and a liquid medium.

[0032] Another aspect of the invention provides a surface treated prepreg composite comprising: a plurality of infiltrated fabric layers stacked in contact with one another to form a multi-ply, fabric reinforced, prepreg composite layup, the prepreg composite layup having a top surface and a bottom surface, each of the infiltrated fabric layers comprising fibers comprising (or consisting essentially of) alumina, silica, mullite, or any combination thereof, the fibers being coated with a coating comprising about 40% to about 85% by weight (weight of coating) aluminum oxide or about 0.1% to about 40% by weight silica (weight of coating); and infiltrated paper covering at least a portion of the top and / or bottom surfaces of the prepreg composite layup, the infiltrated paper being infiltrated with a slurry mixture comprising about 40% to about 85% by weight (weight of slurry) aluminum oxide or about 0.1% to about 40% by weight silica (weight of slurry).

[0033] Another aspect of the invention provides a method of forming a surface treated fabric-reinforced prepreg composite comprising infiltrating an inorganic fabric with a first slurry mixture to form an infiltrated fabric, and drying the infiltrated fabric to form a fabric-reinforced prepreg composite, the first slurry mixture may comprise an oxide component, a liquid medium, and optionally a protonic acid. The method further comprises infiltrating an inorganic paper with a second slurry mixture to form an infiltrated paper, the second slurry mixture comprising an oxide component and a liquid medium, applying the infiltrated paper to a surface of the fabric-reinforced prepreg composite, and drying the infiltrated paper to form a paper-prepreg composite.

[0034] In some implementations, the method further includes stacking one or more layers of paper prepreg composite on an outer surface (e.g., top and / or bottom surface) of the fabric-reinforced prepreg composite to form an alternating paper / fabric / paper prepreg composite layup.

[0035] In some embodiments, the method further comprises stacking two or more layers of the fabric-reinforced prepreg composite to form a multi-ply fabric-reinforced prepreg composite layup. In some embodiments, the method further comprises stacking one or more layers of a paper prepreg composite on a top and / or bottom surface of the multi-ply fabric-reinforced prepreg composite layup to form a paper and multi-ply fabric-reinforced prepreg composite layup. In some embodiments, the method further comprises stacking at least one alternating layer of a paper prepreg composite on a top and bottom surface of the fabric-reinforced prepreg composite to form a stacked alternating paper / cloth / paper prepreg composite layup, the stacked alternating paper / cloth / paper prepreg composite layup comprising at least five alternating layers.

[0036] In some embodiments, the method further comprises autoclaving, oven curing, and / or press curing the infiltrated paper, paper prepreg composite, infiltrated fabric, fabric reinforced prepreg composite, alternating paper / fabric / paper prepreg composite layup, multi-ply fabric reinforced prepreg composite layup, paper and multi-ply fabric reinforced prepreg composite layup, stacked alternating paper / fabric / paper prepreg composite layup, or any combination thereof, into a preform to form a cured ceramic matrix composite article. In some embodiments, the autoclaving, oven curing, and / or press curing is performed at a curing pressure of about 10 psi to about 200 psi. In some embodiments, the method further comprises sintering the cured matrix article to form a fabric reinforced ceramic matrix composite article. In some embodiments, the sintering is performed at a sintering temperature of about 700° C. to about 1,400° C. In some embodiments, the sintering temperature is ramped up to a temperature at a heating rate of about 1° C. / min to about 10° C. / min.

[0037] In some embodiments, the first and / or second slurry mixture is an aqueous slurry comprising about 0.1% to about 40% by weight colloidal silica, about 0.1% to about 10% by weight liquid medium soluble polymer, about 40% to about 85% by weight aluminum oxide powder, optionally sufficient protonic acid (e.g., about 0.1% to about 2% by weight) to adjust the pH of the slurry to a pH of about 3 to about 5, and about 10% to about 60% by weight water. In some embodiments, the first and / or second slurry mixture is an aqueous slurry comprising about 0.1% to about 40% by weight colloidal alumina, about 0.1% to about 10% by weight liquid medium soluble polymer, about 40% to about 80% by weight aluminum oxide powder, optionally about 0.1% to about 2% by weight protonic acid to provide a pH of about 3 to about 5, and about 10% to about 60% by weight water. Weight percentages (wt%) provided herein are by weight of the slurry unless otherwise stated.

[0038] In some embodiments, the first and / or second slurry mixture is an aqueous slurry comprising about 15% to about 30% colloidal silica, about 0.1% to about 4% liquid medium soluble polymer, about 45% to about 65% aluminum oxide powder, about 20% to about 40% water, and optionally, about 0.1% to about 1% protonic acid to provide a pH of about 3 to about 5. In some embodiments, the first and / or second slurry mixture is an aqueous slurry comprising about 15% to about 30% colloidal alumina, about 0.1% to about 4% liquid medium soluble polymer, about 45% to about 65% aluminum oxide powder, about 20% to about 40% water, and optionally, about 0.1% to about 1% protonic acid to provide a pH of about 3 to about 5. Weight percentages (wt %) provided herein are by weight of the slurry unless otherwise stated.

[0039] In some embodiments, the first and / or second slurry mixture is an alcohol-based slurry comprising about 0.1% to about 50% by weight of one or more organic binders including silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof, about 40% to about 85% by weight of aluminum oxide powder, and about 5% to about 60% by weight of alcohol, wherein the alcohol comprises methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C5-C8 alcohols, or any combination thereof. In some embodiments, the first and / or second slurry mixture is an alcohol-based slurry comprising about 5% to about 25% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof, about 45% to about 65% by weight of aluminum oxide powder, and about 30% to about 50% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C5-C8 alcohols, or any combination thereof. Weight percentages (wt%) provided herein are by weight of the slurry unless otherwise stated.

[0040] In some embodiments, the method further comprises compounding the slurry mixture using a high shear mixer, a ball mill, an attritor, a planetary, or any combination thereof.

[0041] In some embodiments, the oxide component comprises aluminum oxide, silicon oxide, boron oxide, zirconium oxide, yttrium oxide, mullite, or any combination thereof. In some embodiments, the oxide component is provided as spheres, hollow spheres, fibers, whiskers, or any combination thereof. In some embodiments, the oxide component is colloidal silica having an average particle diameter of about 1 nanometer to about 10 microns. In some embodiments, the oxide component comprises colloidal alumina having an average particle diameter of about 1 nanometer to about 10 microns. In some embodiments, the liquid medium soluble polymer is polyvinyl alcohol. In some embodiments, the slurry mixture further comprises one or more additives comprising an inorganic polymeric material, an organic polymeric material, one or more surfactants, one or more viscosity modifiers, a glycol, a polyol, or any combination thereof. In some embodiments, the infiltration step is carried out at an infiltration temperature of about 20° C. to about 150° C. In some embodiments, the nonwoven inorganic fabric comprises at least one of a ceramic cloth or a ceramic mat.

[0042] Another aspect of the invention provides a method of forming a fabric-reinforced ceramic matrix composite article, the method comprising infiltrating an inorganic fabric with a first slurry mixture to form an infiltrated fabric, the first slurry mixture may comprise an oxide component, a liquid medium, and optionally a protonic acid; drying the infiltrated fabric to form a fabric-reinforced prepreg composite; and infiltrating an inorganic paper with a second slurry mixture to form an infiltrated paper, the second slurry mixture may comprise an oxide component, a liquid medium, and optionally a protonic acid. applying the infiltrated paper to at least one surface of a fabric-reinforced prepreg composite to form a surface-treated fabric-reinforced prepreg composite; contacting the surface-treated fabric-reinforced prepreg composite to a surface of a preform; curing (e.g., autoclaving, oven-curing, and / or press-curing) the surface-treated fabric-reinforced prepreg composite into the preform to form a cured matrix article; and sintering the cured matrix article to form a fabric-reinforced ceramic matrix composite article.

[0043] Embodiments of this aspect of the invention may include one or more of the following optional features: In some embodiments, the slurry mixture is an aqueous slurry comprising about 0.1% to about 40% by weight colloidal silica, about 0.1% to about 10% by weight liquid medium soluble polymer, about 40% to about 85% by weight aluminum oxide powder, optionally about 0.1% to about 2% by weight protonic acid to provide a pH of about 3 to about 5, and about 10% to about 60% by weight water. In some embodiments, the slurry mixture is an aqueous slurry comprising about 0.1% to about 40% by weight colloidal alumina, about 0.1% to about 10% by weight liquid medium soluble polymer, about 40% to about 85% by weight aluminum oxide powder, optionally about 0.1% to about 2% by weight protonic acid to provide a pH of about 3 to about 5, and about 10% to about 60% by weight water. Weight percentages (wt %) provided herein are by weight of the slurry unless otherwise stated.

[0044] In some embodiments, the slurry mixture is an aqueous slurry comprising about 15% to about 30% colloidal silica, about 0.1% to about 4% liquid medium soluble polymer, about 45% to about 65% aluminum oxide powder, optionally about 0.1% to about 1% protonic acid to provide a pH of about 3 to about 5, and about 20% to about 40% water by weight. In some embodiments, the slurry mixture is an aqueous slurry comprising about 15% to about 30% colloidal alumina, about 0.1% to about 4% liquid medium soluble polymer, about 45% to about 65% aluminum oxide powder, optionally about 0.1% to about 1% protonic acid to provide a pH of about 3 to about 5, and about 20% to about 40% water by weight. Weight percentages (wt %) provided herein are by weight of the slurry unless otherwise stated.

[0045] In some embodiments, the slurry mixture is an alcohol-based slurry comprising about 0.1% to about 50% by weight of one or more organic binders including silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof, about 40% to about 85% by weight of aluminum oxide powder, and about 5% to about 60% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, any C5-C8 alcohol, or any combination thereof. In some embodiments, the slurry mixture is an alcohol-based slurry comprising about 5% to about 25% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; about 45% to about 65% by weight of aluminum oxide powder; and about 30% to about 50% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, any C5-C8 alcohol, or any combination thereof.

[0046] In some embodiments, the method further comprises compounding the slurry mixture using a high shear mixer, a ball mill, an attritor, a planetary, or any combination thereof.

[0047] In some embodiments, the oxide component comprises aluminum oxide, silicon oxide, boron oxide, zirconium oxide, yttrium oxide, mullite, or any combination thereof. In some embodiments, the oxide component comprises spheres, hollow spheres, fibers, or whiskers of any of the above oxide components, or any combination thereof. In some embodiments, the colloidal silica has an average particle diameter of about 1 nanometer to about 10 microns. In some embodiments, the colloidal alumina has an average particle diameter of about 1 nanometer to about 10 microns. In some embodiments, the liquid medium soluble polymer is polyvinyl alcohol. In some embodiments, the slurry mixture further comprises one or more additives comprising an inorganic polymeric material, an organic polymeric material, one or more surfactants, one or more viscosity modifiers, or any combination thereof.

[0048] In some embodiments, the infiltration step is carried out at an infiltration temperature of from about 20°C to about 150°C.

[0049] In some embodiments, autoclaving, oven curing, and / or press curing is carried out at a cure pressure of about 10 psi to about 200 psi.

[0050] In some embodiments, the sintering is carried out at a sintering temperature of about 700° C. to about 1,400° C. In some embodiments, the sintering temperature is reached by ramping at a heating rate of about 1° C. / min to about 10° C. / min.

[0051] In some embodiments, the nonwoven inorganic fabric comprises at least one of a ceramic cloth or a ceramic mat. In some embodiments, the inorganic fabric has a thickness of about 5 mm to about 75 mm. In some embodiments, the inorganic fabric has a weight range of about 10 grams per square meter (gsm) to about 200 gsm prior to infiltration. In some embodiments, the preform comprises a tool, a panel, a support member, a tank, a screen, a shield, a cable, a wire, a fiber, an inorganic article, and an organic article, a layered article, a compounded article, or any combination thereof.

[0052] Another aspect of the invention provides a paper and multi-ply fabric reinforced prepreg composite layup, the paper and multi-ply fabric reinforced prepreg composite layup comprising a plurality of fabric reinforced prepreg composite layers stacked in contact with one another to form the multi-ply fabric reinforced prepreg composite layup, the plurality of fabric reinforced prepreg composite layers comprising a non-woven inorganic fabric, a woven inorganic fiber, or a combination thereof, about 0.1% to about 40% by weight of a colloidal oxide component, about 0.1% to about 10% by weight of a liquid medium soluble polymer, and about 50% to about 99% by weight of an aluminum oxide powder. a plurality of fabric-reinforced prepreg composite layers comprising a paper and a surface layer comprising: a paper and one or more paper prepreg composite layers bonded to the top and bottom surfaces of the multi-ply fabric-reinforced prepreg composite layup to form a multi-ply fabric-reinforced prepreg composite layup, the one or more paper prepreg composite layers comprising an inorganic paper and a second surface layer comprising about 0.1% to about 40% by weight of a colloidal oxide component, about 0.1% to about 10% by weight of a liquid medium-soluble polymer, and about 40% to about 85% by weight of aluminum oxide powder.

[0053] Another aspect of the invention provides a paper and fabric reinforced ceramic matrix composite article comprising a preform that is autoclaved or press cured and sintered into one or more of an infiltrated paper, a paper prepreg composite, an infiltrated fabric, a fabric reinforced prepreg composite, an alternating paper / fabric / paper prepreg composite layup, a multi-ply fabric reinforced prepreg composite layup, a paper and multi-ply fabric reinforced prepreg composite layup, a stacked alternating paper / fabric / paper prepreg composite layup, or any combination thereof, Each prepreg composite comprises at least one surface layer bonded to the infiltrated fabric and / or the infiltrated paper, the surface layer comprising about 0.1% to about 40% by weight of a colloidal oxide component, about 0.1% to about 10% by weight of a liquid medium soluble polymer, and about 40% to about 85% by weight of an aluminum oxide powder.

[0054] Yet another aspect of the invention provides a method of surface treating an inorganic cloth and / or inorganic paper to form a surface treated prepreg composite layup, the method including infiltrating the inorganic cloth with a first slurry mixture to form an infiltrated cloth, the slurry mixture may comprise about 0.1% to about 40% by weight of a colloidal oxide component, about 5% to about 40% by weight of a liquid medium, about 40% to about 85% by weight of an aluminum oxide powder, and optionally a protonic acid; drying the infiltrated cloth to form a cloth reinforced prepreg composite; and infiltrating the inorganic paper with a second slurry mixture to form the infiltrated paper. forming a second slurry mixture, the second slurry mixture may comprise about 0.1% to about 40% by weight of a colloidal oxide component, about 5% to about 40% by weight of a liquid medium, about 40% to about 85% by weight of an aluminum oxide powder, and optionally a protonic acid; drying the infiltrated paper to form a paper prepreg composite; and layering the fabric reinforced prepreg composite with a paper prepreg composite, the at least one layer of the fabric reinforced prepreg composite being stacked alternately with the at least one layer of the paper prepreg composite to form an alternating paper / fabric / paper prepreg composite layup. The alternating paper / fabric / paper prepreg composite layup includes at least one paper prepreg layer on each end of the layup, and the alternating paper / fabric / paper prepreg composite layup includes at least three alternating layers.

[0055] Another aspect of the invention provides a method of treating an inorganic cloth and / or inorganic paper to form a prepreg composite, the method comprising: infiltrating an inorganic cloth with a first slurry mixture to form an infiltrated cloth, the slurry mixture may comprise about 0.1% to about 40% by weight of a colloidal oxide component, about 5% to about 40% by weight of a liquid medium, about 40% to about 85% by weight of an aluminum oxide powder, and optionally a protonic acid; and infiltrating an inorganic paper with a second slurry mixture to form an infiltrated paper, the second slurry mixture may comprise about 0.1% to about 40% by weight of the colloidal oxide component, about 5% to about 40% by weight of a liquid medium, about 40% to about 85% by weight of an aluminum oxide powder, and optionally a protonic acid. the liquid medium may comprise about 5% to about 40% by weight, about 40% to about 85% by weight aluminum oxide powder, and optionally a protonic acid; layering the infiltrated fabric with the infiltrated paper, at least one layer of the infiltrated fabric being stacked alternately with at least one layer of the infiltrated paper to form an alternating infiltrated fabric and paper stack; and drying the alternating infiltrated fabric and paper stack to form an alternating paper / fabric / paper prepreg composite. The alternating paper / fabric / paper prepreg composite includes at least one paper prepreg layer on each end of the layup, and the alternating paper / fabric / paper prepreg composite layup includes at least three alternating layers.

[0056] Another aspect provides a prepreg composite comprising an inorganic fabric and an infiltrant system comprising an oxide component, the infiltrant system being substantially homogeneously dispersed throughout the inorganic fabric.

[0057] In some embodiments, the oxide component comprises aluminum oxide, silicon oxide, boron oxide, zirconium oxide, yttrium oxide, mullite, or any combination thereof.

[0058] In some embodiments, the oxide component comprises spheres, hollow spheres, fibers, whiskers, or any combination thereof.

[0059] In some embodiments, the infiltrant system further comprises colloidal silica or colloidal alumina.

[0060] In some embodiments, the infiltrant system comprises about 0.1 to about 40 weight percent colloidal oxide component, about 0.1 to about 10 weight percent liquid medium soluble polymer, and about 50 to about 99 weight percent aluminum oxide powder. In some embodiments, the infiltrant system comprises about 15 to about 40 weight percent colloidal oxide component, about 0.1 to about 7 weight percent liquid medium soluble polymer, and about 50 to about 80 weight percent aluminum oxide powder.

[0061] In some embodiments, the infiltrant system comprises about 0.1% to about 50% by weight colloidal silica or colloidal alumina, about 0.1% to about 10% by weight liquid medium soluble polymer, and about 40% to about 99% by weight aluminum oxide powder. In some embodiments, the infiltrant system comprises about 15% to about 40% by weight colloidal silica or colloidal alumina, about 0.1% to about 7% by weight liquid medium soluble polymer, and about 50% to about 80% by weight aluminum oxide powder.

[0062] In some embodiments, the infiltrant system comprises about 0.1% to about 60% by weight of one or more organic binders selected from silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof, and about 40% to about 99% by weight of aluminum oxide powder. In some embodiments, the infiltrant system comprises about 15% to about 40% by weight of one or more organic binders selected from silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof, and about 60% to about 85% by weight of aluminum oxide powder.

[0063] In some embodiments, the prepreg composite further comprises an inorganic paper in contact with a surface of the prepreg composite, thereby defining a surface treated prepreg composite, and the infiltrant system is substantially homogeneously dispersed throughout the inorganic paper.

[0064] Another aspect provides a prepreg composite layup comprising two or more prepreg composites stacked in contact with one another.

[0065] In some embodiments, a prepreg composite lay-up comprises one or more layers of inorganic fabric stacked in contact with one another, wherein the infiltrant system is substantially homogeneously dispersed throughout the inorganic fabric, and one or more layers of inorganic paper defining a first surface film, wherein the infiltrant system is substantially homogeneously dispersed throughout the first surface film, the first surface film being stacked on a first side of the one or more layers of inorganic fabric.

[0066] In some embodiments, the prepreg composite layup further comprises one or more layers of inorganic paper defining a second surface film, the infiltrant system being dispersed substantially homogeneously throughout the second surface film, the second surface film being stacked onto a second side of the one or more layers of inorganic fabric.

[0067] In some embodiments, the first side is a front side and the second side is a back side.

[0068] Another aspect provides a ceramic matrix composite article comprising a prepreg composite or prepreg composite lay-up that is autoclaved or press cured and sintered into a preform.

[0069] Other features and advantages of the invention will be apparent from the following detailed description, the figures, and the claims. The present invention provides, for example, the following: (Item 1) 1. A method of forming a surface treated fabric reinforced prepreg composite, the method comprising: infiltrating an inorganic fabric with a first slurry mixture to form an infiltrated fabric, the first slurry mixture comprising an oxide component and a liquid medium; infiltrating the inorganic paper with a second slurry mixture to form an infiltrated paper, the second slurry mixture comprising an oxide component and a liquid medium; applying the infiltrated paper to a surface of the infiltrated fabric to form a surface treated fabric reinforced prepreg composite; A method comprising: (Item 2) 2. The method of claim 1, further comprising drying the infiltrated fabric prior to applying the infiltrated paper to a surface of the infiltrated fabric. (Item 3) 2. The method of claim 1, further comprising simultaneously drying the infiltrated fabric and the infiltrated paper. (Item 4) 4. The method of any one of claims 1-3, wherein the inorganic cloth comprises a plurality of fibers comprising alumina, silica, mullite, zirconia, or any combination thereof. (Item 5) 5. The method according to any one of items 1 to 4, wherein the inorganic cloth has a thickness of about 5 mm to about 75 mm before being infiltrated with the first slurry mixture. (Item 6) 6. The method of any one of items 1-5, wherein the inorganic fabric is woven, non-woven, or any combination thereof. (Item 7) 7. The method of any one of claims 1-6, wherein the inorganic paper comprises alumina, silica, mullite, zirconia, or any combination thereof. (Item 8) 8. The method according to any one of items 1-7, wherein the inorganic paper has a thickness of about 0.1 mm to about 4.99 mm before being infiltrated with the second slurry mixture. (Item 9) 9. The method of any one of claims 1-8, wherein the oxide component of the first slurry mixture and / or the second slurry mixture comprises one or more oxides of aluminum, silicon, boron, zirconium, yttrium, or any combination thereof. (Item 10) 10. The method of claim 9, wherein the one or more oxides of the first slurry mixture and / or the second slurry mixture are provided as particles comprising spheres, hollow spheres, fibers, whiskers, or any combination thereof. (Item 11) 11. The method of claim 9 or 10, wherein the first slurry mixture and / or the second slurry mixture further comprises colloidal silica having an average particle diameter of about 1 nanometer to about 10 microns. (Item 12) 11. The method of claim 9 or 10, wherein the first slurry mixture and / or the second slurry mixture further comprises colloidal alumina having an average particle diameter of about 1 nanometer to about 10 microns. (Item 13) 13. The method of any one of items 1-12, wherein the liquid medium of the first slurry mixture and / or the second slurry mixture is water, alcohol, or any combination thereof. (Item 14) The first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture, and the aqueous slurry mixture comprises: About 0.1% by weight to about 40% by weight of colloidal silica; about 0.1% to about 10% by weight of a liquid medium soluble polymer; About 40% by weight to about 85% by weight of aluminum oxide powder; About 10% to about 60% by weight of water 10. The method according to any one of items 1 to 9, comprising: (Item 15) The first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture, and the aqueous slurry mixture comprises: About 15 to about 30 weight percent colloidal silica; about 0.1 to about 4 weight percent of a liquid medium soluble polymer; about 45 to about 65 weight percent aluminum oxide powder; About 20 to about 40% by weight of water Item 15. The method of item 14, comprising: (Item 16) 11. The method of claim 9 or 10, wherein the liquid medium soluble polymer is polyvinyl alcohol. (Item 17) The first slurry mixture and / or the second slurry mixture is an alcohol-based slurry, and the alcohol-based slurry is about 0.1% to about 50% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; About 40% by weight to about 85% by weight of aluminum oxide powder; about 5% to about 60% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C5-C8 alcohols, or any combination thereof; 10. The method according to any one of items 1 to 9, comprising: (Item 18) The first slurry mixture and / or the second slurry mixture is an alcohol-based slurry, and the alcohol-based slurry is about 5% to about 25% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; About 45% to about 65% by weight of aluminum oxide powder; about 30% to about 50% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C5-C8 alcohols, or any combination thereof; Item 18. The method of item 17, comprising: (Item 19) 19. The method according to any one of items 1-18, wherein the pH of the first slurry mixture and / or the second slurry mixture is adjusted to a pH of about 3 to about 5 using a protonic acid. (Item 20) 20. The method of any one of items 1-19, wherein the first slurry mixture and / or the second slurry mixture further comprises about 0.1 wt % to about 2 wt % of a protonic acid. (Item 21) 21. The method of claim 20, wherein the first slurry mixture and / or the second slurry mixture further comprises about 0.1% to about 1% by weight of a protonic acid. (Item 22) 22. The method of any one of items 1-21, wherein the first slurry mixture and / or the second slurry mixture further comprise one or more additives, the one or more additives comprising an inorganic polymeric material, an organic polymeric material, one or more surfactants, one or more viscosity modifiers, a glycol, a polyol, or any combination thereof. (Item 23) 23. The method of any one of items 1-22, further comprising curing the fabric reinforced prepreg composite at a pressure of about 10 psi to about 200 psi and a temperature of about 75° C. to about 500° C. (Item 24) 24. The method of claim 23, further comprising sintering the fabric-reinforced prepreg composite at a sintering temperature of about 700°C to about 1,400°C. (Item 25) 25. The method of claim 24, wherein the sintering is carried out using a heating rate of about 1° C. / min to about 10° C. / min until the sintering temperature is achieved. (Item 26) 25. The method of any one of items 1-24, further comprising blending the first slurry mixture and / or the second slurry mixture using a high shear mixer, a ball mill, an attritor, a planetary, or any combination thereof. (Item 27) 27. The method according to any one of items 1-26, wherein the inorganic cloth is infiltrated with the first slurry mixture heated to an infiltration temperature of about 20° C. to about 150° C., and / or the inorganic paper is infiltrated with the second slurry mixture heated to an infiltration temperature of about 20° C. to about 150° C. (Item 28) 1. A method of forming a fabric-reinforced ceramic matrix composite article, the method comprising: providing a prepreg composite comprising one or more layers of infiltrated fabric, the infiltrated fabric comprising an inorganic fabric infiltrated with a first slurry mixture comprising an oxide component and a liquid medium; contacting the prepreg composite with a surface of a preform; applying an infiltrated paper to at least one surface of the prepreg composite to form a surface treated prepreg composite, the infiltrated paper comprising inorganic paper infiltrated with a second slurry mixture comprising an oxide component and a liquid medium; sintering the surface treated prepreg composite at a sintering temperature of about 700°C to about 1,400°C to form the fabric reinforced ceramic matrix composite article. A method comprising: (Item 29) 1. A method of forming a fabric-reinforced ceramic matrix composite article, the method comprising: providing a prepreg composite comprising one or more layers of infiltrated fabric, the infiltrated fabric comprising an inorganic fabric infiltrated with a first slurry mixture comprising an oxide component and a liquid medium; contacting the prepreg composite with a surface of a preform; applying an infiltrated paper to at least one surface of the prepreg composite to form a surface treated prepreg composite, the infiltrated paper comprising inorganic paper infiltrated with a second slurry mixture comprising an oxide component and a liquid medium; curing the surface treated prepreg composite at a pressure of about 10 psi to about 200 psi and a temperature of about 75° C. to about 500° C.; sintering the surface treated prepreg composite at a sintering temperature of about 700°C to about 1,400°C to form the fabric reinforced ceramic matrix composite article. A method comprising: (Item 30) 1. A method of forming a fabric-reinforced ceramic matrix composite article, the method comprising: providing a prepreg composite comprising one or more layers of infiltrated fabric, the infiltrated fabric comprising an inorganic fabric infiltrated with a first slurry mixture comprising an oxide component and a liquid medium; curing the prepreg composite at a pressure of about 10 psi to about 200 psi and a temperature of about 75° C. to about 500° C. to form a cured prepreg composite; applying an infiltrated paper to at least one surface of the cured prepreg composite to form a surface treated prepreg composite, the infiltrated paper comprising inorganic paper infiltrated with a second slurry mixture comprising an oxide component and a liquid medium; sintering the surface treated prepreg composite at a sintering temperature of about 700°C to about 1,400°C to form the fabric reinforced ceramic matrix composite article. A method comprising: (Item 31) 31. The method of any one of claims 28-30, wherein the inorganic cloth comprises a plurality of fibers comprising alumina, silica, mullite, zirconia, or any combination thereof. (Item 32) 32. The method of any one of items 28-31, wherein the inorganic cloth has a thickness of about 5 mm to about 75 mm before being infiltrated with the first slurry mixture. (Item 33) 33. The method of any one of items 28-32, wherein the inorganic fabric is woven, non-woven, or any combination thereof. (Item 34) 34. The method of any one of claims 28-33, wherein the inorganic paper comprises alumina, silica, mullite, zirconia, or any combination thereof. (Item 35) The method of any one of items 28-343, wherein the inorganic paper has a thickness of about 0.1 mm to about 4.99 mm before being infiltrated with the second slurry mixture. (Item 36) 36. The method of any one of claims 28-35, wherein the oxide component of the first slurry mixture and / or the second slurry mixture comprises one or more oxides of aluminum, silicon, boron, zirconium, yttrium, or any combination thereof. (Item 37) Item 37. The method of item 36, wherein the one or more oxides of the first slurry mixture and / or the second slurry mixture are provided as particles comprising spheres, hollow spheres, fibers, whiskers, or any combination thereof. (Item 38) 38. The method of claim 36 or 37, wherein the first slurry mixture and / or the second slurry mixture further comprises colloidal silica having an average particle diameter of about 1 nanometer to about 10 microns. (Item 39) Item 38. The method of item 36 or item 37, wherein the first slurry mixture and / or the second slurry mixture further comprises colloidal alumina having an average particle diameter of about 1 nanometer to about 10 microns. (Item 40) 40. The method of any one of items 28-39, wherein the liquid medium of the first slurry mixture and / or the second slurry mixture is water, alcohol, or any combination thereof. (Item 41) The first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture, and the aqueous slurry mixture comprises: About 0.1% by weight to about 40% by weight of colloidal silica; about 0.1% to about 10% by weight of a liquid medium soluble polymer; About 40% by weight to about 85% by weight of aluminum oxide powder; About 10% to about 60% by weight of water 37. The method according to any one of items 28-36, comprising: (Item 42) The first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture, and the aqueous slurry mixture comprises: About 15 to about 30 weight percent colloidal silica; about 0.1 to about 4 weight percent of a liquid medium soluble polymer; about 45 to about 65 weight percent aluminum oxide powder; About 20 to about 40% by weight of water Item 42. The method of item 41, comprising: (Item 43) 43. The method of claim 41 or 42, wherein the liquid medium soluble polymer is polyvinyl alcohol. (Item 44) The first slurry mixture and / or the second slurry mixture is an alcohol-based slurry, and the alcohol-based slurry is about 0.1% to about 50% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; About 40% by weight to about 85% by weight of aluminum oxide powder; about 5% to about 60% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C5-C8 alcohols, or any combination thereof; 37. The method according to any one of items 28-36, comprising: (Item 45) The first slurry mixture and / or the second slurry mixture is an alcohol-based slurry, and the alcohol-based slurry is about 5% to about 25% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; About 45% to about 65% by weight of aluminum oxide powder; about 30% to about 50% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C5-C8 alcohols, or any combination thereof; Item 45. The method of item 44, comprising: (Item 46) 46. ​​The method of any one of items 28-45, wherein the pH of the first slurry mixture and / or the second slurry mixture is adjusted to a pH of about 3 to about 5 using a protonic acid. (Item 47) 46. ​​The method of any one of items 28-45, wherein the first slurry mixture and / or the second slurry mixture further comprises about 0.1 wt % to about 2 wt % of a protonic acid. (Item 48) Item 48. The method of claim 47, wherein the first slurry mixture and / or the second slurry mixture further comprises about 0.1% to about 1% by weight of a protonic acid. (Item 49) 49. The method of any one of items 28-48, wherein the first slurry mixture and / or the second slurry mixture further comprise one or more additives, the one or more additives comprising an inorganic polymeric material, an organic polymeric material, one or more surfactants, one or more viscosity modifiers, a glycol, a polyol, or any combination thereof. (Item 50) 50. The method according to any one of items 28-49, wherein the sintering is carried out using a heating rate of about 1° C. / min to about 10° C. / min until the sintering temperature is achieved. (Item 51) A surface-treated prepreg composite, the surface-treated prepreg composite comprising: an infiltrated fabric having a top layer and a bottom layer, the infiltrated fabric comprising fibers comprising alumina, silica, mullite, or any combination thereof, the top layer and the bottom layer forming a coating on the infiltrated fabric, each surface layer comprising about 40% to about 85% by weight (by weight of the surface layer) aluminum oxide or about 0.1% to about 40% by weight (by weight of the surface layer); an infiltrated paper substantially covering and in contact with the top and / or bottom layers of said infiltrated fabric; Equipped with 1. A surface treated prepreg composite, wherein the infiltrated paper comprises fibers comprising alumina, silica, mullite, or any combination thereof, and the infiltrated paper is infiltrated with a slurry mixture comprising an oxide component and a liquid medium. (Item 52) A surface-treated prepreg composite, the surface-treated prepreg composite comprising: a plurality of infiltrated fabric layers stacked in contact with one another, the plurality of infiltrated fabric layers forming a multi-ply fabric reinforced prepreg composite lay-up, the prepreg composite lay-up having a top surface and a bottom surface, each of the infiltrated fabric layers comprising fibers comprising alumina, silica, mullite, or any combination thereof, the fibers being at least partially coated with the coating comprising about 40% to about 85% by weight (by weight of the coating) aluminum oxide or about 0.1% to about 40% by weight silica (by weight of the coating); an infiltrated paper covering at least a portion of the top and / or bottom surfaces of the prepreg composite lay-up; Equipped with A surface treated prepreg composite, wherein the infiltrated paper is infiltrated with the slurry mixture comprising about 40% to about 85% by weight (by weight of the slurry) aluminum oxide or about 0.1% to about 40% by weight (by weight of the slurry). [Brief description of the drawings]

[0070] The following figures are provided as examples and are not intended to limit the scope of the claimed invention.

[0071] [Figure 1] FIG. 1 is a flow diagram illustrating a method of forming a fabric-reinforced ceramic matrix composite article in accordance with an implementation of the present invention.

[0072] [Diagram 2] FIG. 2 is a cross-sectional schematic diagram of an alternating paper and fabric reinforced prepreg composite layup according to one aspect of the present invention.

[0073] [Diagram 3] FIG. 3 is a cross-sectional schematic diagram of a stacked alternating paper and fabric reinforced prepreg composite layup according to one aspect of the present invention.

[0074] [Figure 4] FIG. 4 is a cross-sectional schematic diagram of a multi-ply fabric-reinforced prepreg composite lay-up according to one aspect of the invention.

[0075] [Diagram 5] FIG. 5 is a cross-sectional schematic diagram of a paper and multi-ply fabric reinforced prepreg composite lay-up according to one aspect of the invention.

[0076] [Figure 6] FIG. 6 is a cross-sectional schematic diagram of a multi-ply paper prepreg composite lay-up according to one aspect of the present invention.

[0077] [Figure 7] FIG. 7 is a cross-sectional scanning electron microscope (SEM) image of a paper and multi-ply fabric reinforced prepreg composite according to one aspect of the invention.

[0078] [Figure 8] FIG. 8 is a cross-sectional SEM image of a paper and multi-ply fabric reinforced prepreg composite according to one aspect of the present invention.

[0079] [Figure 9] FIG. 9 is a cross-sectional SEM image of a paper and multi-ply fabric reinforced prepreg composite according to one aspect of the present invention.

[0080] [Figure 10A] FIG. 10A is a tool side photographic image of a paper and multi-ply fabric reinforced prepreg composite according to one aspect of the present invention.

[0081] [Figure 10B] FIG. 10B is a bag side photographic image of a paper and multi-ply fabric reinforced prepreg composite according to one aspect of the present invention.

[0082] [Figure 11] FIG. 11 is a bar graph of line roughness for the samples of Example 1 and the corresponding control samples.

[0083] [Figure 12] FIG. 12 is a bar graph of surface roughness for the samples of Example 1 and the corresponding control samples.

[0084] [Figure 13] FIG. 13 is a bar graph of the dielectric constant values ​​for the samples of Example 1 and the corresponding control samples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0085] The present invention provides a surface treated fabric reinforced prepreg composite and a method of surface treating an inorganic fabric with an inorganic paper to form a reinforced prepreg composite, the method includes infiltrating the inorganic fabric with a first slurry mixture to form an infiltrated fabric, infiltrating the inorganic paper with a second slurry mixture to form an infiltrated paper, and applying the infiltrated paper to at least one surface of the infiltrated fabric. Some embodiments include drying the infiltrated fabric prior to applying the infiltrated paper to form a fabric reinforced prepreg composite. Some embodiments also include drying the infiltrated paper prior to applying the infiltrated paper to the fabric reinforced prepreg composite.

[0086] (I. Definition)

[0087] As used herein, the following definitions shall apply unless otherwise indicated.

[0088] As used herein, the term "fabric" refers to a textile material consisting of mechanically interlocked fibers or filaments, the textile material having a thickness of 5 mm or more prior to infiltration. The textile material may be randomly integrated (nonwoven) or closely oriented with warp and filler strands at right angles to each other (woven). The term "fabric" typically refers to wool, cotton, or other synthetic fibers, but fabrics as used herein can be made from inorganic materials including, but not limited to, glass (including insulating or E-glass), alumina (aluminum oxide), mullite, silica (silicon dioxide), microglass, carbon (including graphite), activated carbon, aramid, Meerschaum (hydrated magnesium silicate), potassium titanate, wollastonite (calcium silicate), poly-p-phenylene-benzoxazole (PBO), alumina-silica, rock wool, boron, quartz, basalt, ceramics, and combinations thereof.

[0089] As used herein, the term "paper" refers to an inorganic material formed from randomly oriented inorganic fibers, such as ceramic fibers, which have been chemically treated to form a sheet or mat having a thickness of less than 5 mm prior to infiltration. A wide variety of sources have been used for such inorganic papers, including, but not limited to, glass (including insulating or E-glass), microglass, alumina, silica, carbon (including graphite), activated charcoal, aramid, Meersham (hydrated magnesium silicate), potassium titanate, wollastonite (calcium silicate), poly-p-phenylene-benzoxazole (PBO), alumina-silica, rock wool, boron, quartz, basalt, ceramic, and combinations thereof. Paper can be produced using a variety of different methods, but typically includes the following steps: 1) producing inorganic fibers with the desired material properties for the paper, 2) adding fillers or other additives to the inorganic fibers, 3) forming a paper sheet on a machine used to turn and dry the inorganic paper, 4) calendering to obtain the desired thickness of the paper, and 5) coating the paper for final finishing.

[0090] Although paper and fabric can be formed from the same fibers, paper is distinguished from nonwoven fabrics in that paper has a thickness below 5 mm while fabric has a thickness of 5 mm or more, and the thickness of each of these materials is evaluated prior to infiltration under ambient conditions.

[0091] As used herein, the term "slurry" means a fluid mixture (eg, a mechanical mixture) comprising solid particles suspended in a liquid medium.

[0092] As used herein, the term "infiltrate" means to penetrate, adsorb, or wet. In some cases, the act of infiltrating can be accomplished by contacting (e.g., drop casting, painting, dipping, spraying, etc.) an inorganic paper or fabric (e.g., an inorganic woven or nonwoven fabric) with a liquid or slurry such that a portion of the liquid or slurry penetrates, adsorbs, wets, or is otherwise drawn into at least a portion of the inorganic paper or fabric.

[0093] As used herein, the term "prepreg composite" refers to a partially dried or dried infiltrated fabric (i.e., an infiltrated inorganic fabric) formed by infiltrating an inorganic fabric with a slurry mixture comprising an oxide component (e.g., an oxide of aluminum, boron, zirconium, or silicon, or mullite) and a liquid. The prepreg composite can be subjected to heat (e.g., sintering) and other processing conditions to form a ceramic matrix composite comprising a cured (or substantially rigid) workpiece.

[0094] As used herein, the term "mullite" refers to a compound comprising SiO and AlO, which are present in the stoichiometric amounts of 3AlO2SiO or 2AlOSiO. Mullite also includes zirconium-coated mullite.

[0095] As used herein, the term "layup" refers to a layered or stacked material formed from one or more layers (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 1-3, 2-4, 1-5, or 2-5 layers) of prepreg composite, where the layered or stacked material has not been subjected to a final heat treatment (e.g., sintering) to form a cured (e.g., substantially rigid) workpiece. For example, each layer of prepreg composite in a layup has been dried (or partially dried) but has not been thermally treated to form a cured workpiece. Other examples of layups include materials formed from one or more layers of prepreg composite and one or more layers of infiltrated paper, where the infiltrated paper constitutes an outer surface of the layup. In other examples, the infiltrated paper is interleaved between layers of prepreg composite to form a layup having a series of alternating layers.

[0096] As used herein, the term "protic acid" refers to an acid that forms hydrogen cations in aqueous solution. Examples of protic acids include hydrogen halides (e.g., HCl, HBr, HF, and HI), acetic acid, sulfuric acid, phosphoric acid, and the like.

[0097] As used herein, the phrase "stable or chemically feasible" refers to compounds and materials that are substantially unaltered when exposed to conditions to enable their production, detection, and preferably their recovery, purification, and use for one or more of the purposes disclosed herein. In some embodiments, a stable or chemically feasible compound is one that is substantially unaltered when exposed to temperatures of 40° C. or less in the absence of moisture or other chemically reactive conditions for at least one week.

[0098] As used herein, the term "and / or," when used in a list of two or more items, means that any one of the listed items may be taken by itself, or any combination of two or more of the listed items may be taken. For example, if a composition is described as containing components A, B, and / or C, the composition may contain A alone, B alone, C alone, A and B in combination, A and C in combination, B and C in combination, or A, B, and C in combination.

[0099] It should be noted that the use of the descriptive terms "first," "second," "third," etc. are used to distinguish separate elements (e.g., solvents, reaction steps, processes, reagents, etc.) and may or may not refer to the relative order or relative chronology of the elements being described.

[0100] (II. Prepreg Materials)

[0101] One aspect of the invention provides a layup comprising an infiltrated inorganic paper layer bonded to at least one outer surface of a prepreg composite or stack of prepreg composites, the prepreg composite being formed from an inorganic fabric (woven or nonwoven) infiltrated with a first slurry mixture comprising about 0.1% to about 40% by weight of an oxide component (e.g., colloidal oxide component), about 0.1% to about 10% by weight of a liquid medium soluble polymer, and about 50% to about 99% by weight of aluminum oxide powder, the inorganic paper being infiltrated with a second slurry mixture comprising about 0.1% to about 40% by weight of an oxide component (e.g., colloidal oxide component), about 0.1% to about 10% by weight of a liquid medium soluble polymer, and about 50% to about 99% by weight of aluminum oxide powder.

[0102] (A. Inorganic fabric base material)

[0103] The cloth substrates useful in the methods, surface-treated prepreg composites, and surface-treated CMC materials of the present invention include inorganic cloths (e.g., nonwoven inorganic cloths, woven inorganic cloths, or any combination thereof). These various inorganic cloths include inorganic fibers that provide structural reinforcement in the fabricated composite substrates (e.g., prepreg composites and CMC materials), and these inorganic fibers can take the form of chopped fibers, continuous fibers, filaments, tows, bundles, sheets, plies, or any combination thereof. The continuous fibers can further adopt any of unidirectional (aligned in one direction), multidirectional (aligned in different directions), nonwoven, woven, knitted, stitched, wound, needled, and braided configurations, and swirl mat, felt mat, and chopped mat structures. Woven fiber structures include multiple woven tows, each of which can be composed of multiple filaments, e.g., tens, hundreds, or thousands of filaments.

[0104] In some aspects, the inorganic fabric comprises one or more inorganic fibers comprised of glass (including insulating or E-glass), microglass, carbon (including graphite), activated charcoal, aramid, Meersham (hydrated magnesium silicate), potassium titanate, wollastonite (calcium silicate), poly-p-phenylene-benzoxazole (PBO), alumina, silica, alumina-silica, rock wool, boron, quartz, basalt, ceramic, mullite, and any combination thereof.

[0105] In some aspects, the fabric may include a nonwoven ceramic fabric in the form of a mat, blanket, board, or felt and may comprise fibers of aluminum oxide, silicon oxide, mullite, and / or other inorganic fibers. In such embodiments, the inorganic fibers of the fabric may range from about 40% to about 100% by weight aluminum oxide fibers, about 0% to about 60% by weight silicon oxide fibers, about 1% to about 100% by weight mullite, and / or about 0% to about 50% other inorganic fibers. These weight percentages are given by weight of the fabric.

[0106] The inorganic fabric used in the present invention has a thickness of 5 mm or more (e.g., 5 mm to about 100 mm, 5 mm to about 75 mm, 5 mm to about 50 mm, about 10 mm to about 50 mm, about 10 mm to about 30 mm, about 10 mm to about 25 mm, or about 6 mm to about 25 mm). The thickness of the inorganic fabric is determined under ambient conditions prior to infiltration.

[0107] In some aspects, the inorganic fabric can include an inorganic binder, hi other aspects, the inorganic fabric is substantially free of any inorganic or organic binders.

[0108] In some aspects, the inorganic fabric may be needled to impart increased flexibility to the fabric.

[0109] In some aspects, the inorganic fabric comprises, is formed of, or consists essentially of alumina (e.g., polycrystalline alumina) fibers, silica fibers, mullite fibers, or other ceramic fibers. For example, the inorganic fabric comprises, is formed of, or consists essentially of alumina (e.g., polycrystalline alumina) fibers, silica fibers, mullite fibers, or any combination thereof.

[0110] Commercially available examples of inorganic fabrics include, but are not limited to, DENKA® ALCEN® blankets, DENKA® ALCEN® felt, MAFTEC® MLS blankets, CEREMATERIALS® ceramic blankets, UNIFRAX® FIBERFRAX® ceramic mats, and UNIFRAX® FIBERFRAX® ceramic blankets.

[0111] In some aspects, the inorganic fabric comprises a DENKA® ALCEN® blanket, a DENKA® ALCEN® felt, a MAFTEC® MLS blanket, a CEREMATERIALS® ceramic blanket, a UNIFRAX® FIBERFRAX® ceramic mat, a UNIFRAX® FIBERFRAX® ceramic blanket, or any combination thereof.

[0112] In some aspects, the inorganic fabric is thermally stable and capable of maintaining its mechanical properties at standard operating temperatures of about 700° C. to about 1,600° C., about 800° C. to about 1,400° C., or about 700° C. to about 1,200° C. In some aspects, the woven and / or nonwoven inorganic fabric has a tensile strength of at least 50 psi, at least 75 psi, at least 100 psi, at least 125 psi, at least 150 psi, or at least 200 psi at its standard operating temperatures.

[0113] In some aspects, the inorganic fabric has a loss on ignition of less than about 25%, less than about 15%, less than about 10%, or less than about 5%. For example, the inorganic fabric has a loss on ignition of about 0.001% to about 10% (e.g., about 0.01% to about 5%). In some aspects, the inorganic fabric has a heat shrinkage at a processing temperature of less than about 20%, less than about 15%, less than about 10%, less than about 8%, less than about 6%, less than about 5%, or less than about 4%. For example, the inorganic fabric has a heat shrinkage at a processing temperature of about 0.001% to about 10% (e.g., about 0.01% to about 5%).

[0114] (B. Inorganic paper base material)

[0115] The inorganic paper substrates useful for surface treatment of the prepreg composites, CMC materials, and methods disclosed herein comprise non-woven randomly oriented inorganic fibers that provide structural reinforcement in the surface treated prepreg composites and layups thereof, and these inorganic fibers can be in the form of chopped fibers, continuous fibers, filaments, tows, bundles, sheets, plies, or any combination thereof.

[0116] In some aspects, the fibers of the inorganic paper may include, but are not limited to, glass (including insulating or E-glass), microglass, carbon (including graphite), activated charcoal, alumina, silica, Meersham (hydrated magnesium silicate), potassium titanate, wollastonite (calcium silicate), poly-p-phenylene-benzoxazole (PBO), alumina-silica, mullite, rock wool, boron, quartz, basalt, ceramic, or any combination thereof.

[0117] In some aspects, the inorganic paper comprises, is formed of, or consists essentially of alumina (e.g., polycrystalline alumina) fibers, silica fibers, mullite fibers, or other ceramic fibers. For example, the inorganic paper comprises, is formed of, or consists essentially of alumina (e.g., polycrystalline alumina) fibers, silica fibers, mullite fibers, or any combination thereof.

[0118] In some aspects, the inorganic paper can comprise fibers comprising aluminum oxide, silicon dioxide, and / or other inorganic fibers. In such embodiments, the inorganic fibers of the paper can range from about 40% to about 100% aluminum oxide fibers, about 0% to about 60% silicon dioxide fibers, and / or about 0% to about 50% other inorganic fibers.

[0119] The inorganic paper useful in the present invention has a thickness of less than 5 mm. For example, the inorganic paper has a thickness of 0.05 mm to about 4 mm, about 0.10 mm to about 3.5 mm, about 0.5 mm to about 3.0 mm, about 0.1 mm to about 1 mm, or about 0.75 mm to about 2.75 mm. The thickness of the inorganic paper is determined under ambient conditions prior to infiltration.

[0120] In some aspects, the inorganic paper can include an inorganic binder, an inorganic filler, or a combination thereof. In some aspects, the inorganic filler can include, for example, but not limited to, precipitated calcium carbonate (PCC), ground calcium carbonate (GCC), calcium carbonate, kaolin clay, talc, titanium dioxide (TiO2), alumina trihydrate, alumina, precipitated silica, silicate (PSS), and combinations thereof.

[0121] In some aspects, the inorganic paper may include, for example, but not limited to, DENKA® ALCEN® paper, SAFFIL® paper, 3M® CEQUIN® paper, CEREMATERIALS® ceramic paper, UNIFRAX® FIBERFRAX® paper, or combinations thereof.

[0122] In some aspects, the inorganic paper is thermally stable and can maintain its mechanical properties at standard operating temperatures of about 700°C to about 1,600°C, about 800°C to about 1,400°C, or about 700°C to about 1,200°C. In some aspects, the inorganic paper has a tensile strength of at least 50 psi, at least 75 psi, at least 100 psi, at least 125 psi, at least 150 psi, or at least 200 psi at its standard operating temperature. In some aspects, the inorganic paper has a loss on ignition of less than about 25%, less than about 15%, less than about 10%, or less than about 5%. For example, the inorganic paper has a loss on ignition of about 0.01% to about 5%. In some aspects, the inorganic paper has a heat shrinkage at a processing temperature of less than about 20%, less than about 15%, less than about 10%, less than about 8%, less than about 6%, less than about 5%, or less than about 4%. For example, inorganic paper has a thermal shrinkage rate at a processing temperature of about 0.01% to about 5%.

[0123] (C. Slurry Mixture)

[0124] The slurries useful in the methods and materials of the present invention can infiltrate and / or penetrate inorganic paper, inorganic cloth, or any combination thereof. In some aspects, the slurries can include a first slurry used to infiltrate the inorganic cloth and a second slurry used to infiltrate the inorganic paper. The number of slurry mixtures used and their respective labels are not meant to be limiting, but simply specify that one or more slurry mixtures can be used to infiltrate, coat, penetrate, soak, cover, fill, and / or penetrate inorganic paper, inorganic cloth, or any combination thereof. In some aspects, a single slurry mixture or composition can be used to infiltrate both inorganic cloth and inorganic paper. In other aspects, different slurry mixtures can be used for each of the inorganic cloth and inorganic paper. In still other aspects, a combination of different slurry mixtures can be used to infiltrate each of the inorganic cloth and inorganic paper depending on the desired application of the final CMC material.

[0125] In some aspects, the slurry mixture comprises an oxide component. The oxide component can comprise oxides of aluminum, silicon, boron, sodium, calcium, etc., or any combination thereof. In some examples, the oxide component of the slurry mixture comprises a combination of aluminum oxide, silicon oxide, boron oxide, mullite, etc., provided as powders or particles (e.g., solid spheres, hollow spheres, fibers, whiskers, or any combination thereof) suspended in a liquid (under ambient conditions). The oxide component particles used in the slurry mixture can be spherical in shape and have an average particle size ranging from about 0.1 nanometers to about 10 microns, about 1 nanometer to about 10 microns, or about 10 nanometers to about 10 microns as measured by light scattering or optical microscopy. In some aspects, the oxide component comprises or consists essentially of aluminum oxide, silicon oxide, boron oxide, zirconium oxide, yttrium oxide, mullite, or any combination thereof. In yet other aspects, the oxide component is comprised of particles (e.g., solid spheres, hollow spheres, fibers, whiskers, or any combination thereof) provided in the slurry mixture. In some aspects, the weight percent concentration of the oxide component in the slurry is about 40% to about 85%, about 45% to about 75%, about 45% to about 65%, or about 50% to about 85% by weight of the slurry mixture.

[0126] In some aspects, the liquid of the slurry comprises water, methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, glycerol, ethylene glycol, propylene glycol, C5-C8 linear or branched alkyl alcohols, polyols, or any combination thereof. In some aspects, the weight percent concentration of the liquid in the slurry is about 5% to about 60%, about 15% to about 60%, about 25% to about 50%, about 5% to about 20%, about 35% to about 45%, about 20% to about 40%, about 30% to about 50%, or about 40% to about 60% by weight.

[0127] In some aspects, the slurry comprises a stabilizing agent, such as an organic and / or inorganic polymeric material and / or a polymer emulsion. In some aspects, the liquid medium soluble polymer is polyvinyl alcohol. In some aspects, the slurry mixture further comprises one or more additives comprising an inorganic polymeric material, an organic polymeric material, one or more surfactants, one or more viscosity modifiers, or any combination thereof.

[0128] In some aspects, the slurry comprises a protonic acid. For example, the protonic acid is added to the slurry mixture in an amount sufficient to provide the slurry with a pH of about 3 to about 5. In some examples, the protonic acid is hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, hydrogen fluoride, hydrogen bromide, acetic acid, nitric acid, formic acid, or any combination thereof. In some aspects, the slurry mixture can be made substantially homogeneous by applying high shear mixing or a milling process, including, for example, a ball mill, an attritor, or a planetary mill.

[0129] In some aspects, the slurry mixture is an aqueous slurry comprising about 0.1% to about 40% by weight colloidal silica, about 0.1% to about 10% by weight liquid medium soluble polymer, about 40% to about 85% by weight aluminum oxide powder, optionally about 0.1% to about 2% by weight protonic acid, and about 10% to about 60% by weight water.

[0130] In some embodiments, the slurry mixture is an aqueous slurry comprising about 15% to about 30% by weight colloidal silica, about 0.1% to about 4% by weight liquid medium soluble polymer, about 45% to about 65% by weight aluminum oxide powder, optionally about 0.1% to about 1% by weight protonic acid, and about 20% to about 40% by weight water.

[0131] In another aspect, the slurry mixture is an aqueous slurry comprising about 0.1% to about 40% by weight colloidal alumina, about 0.1% to about 10% by weight liquid medium soluble polymer, about 40% to about 80% by weight aluminum oxide powder, optionally about 0.1% to about 2% by weight protonic acid, and about 10% to about 60% by weight water.

[0132] In some embodiments, the slurry mixture is an aqueous slurry comprising about 15% to about 30% by weight colloidal alumina, about 0.1% to about 4% by weight liquid medium soluble polymer, about 45% to about 65% by weight aluminum oxide powder, optionally about 0.1% to about 1% by weight protonic acid, and about 20% to about 40% by weight water.

[0133] In yet another aspect, the slurry mixture is an alcohol-based slurry comprising about 0.1% to about 50% by weight of one or more organic binders including silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof, about 40% to about 85% by weight of aluminum oxide powder, about 5% to about 60% by weight of alcohol, optionally about 0.1% to about 10% by weight of a liquid medium soluble polymer, and optionally about 0.1% to about 2% by weight of a protonic acid, wherein the alcohol comprises methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, a C5-C8 alcohol, or any combination thereof.

[0134] In some embodiments, the slurry mixture is an alcohol-based slurry comprising about 5% to about 25% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; about 45% to about 65% by weight of aluminum oxide powder; and about 30% to about 50% by weight of alcohol, the alcohol comprising methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, any C5-C8 alcohol, or any combination thereof.

[0135] In yet another aspect, the slurry mixture comprises about 0.1 wt % to about 40 wt % colloidal oxide component (e.g., colloidal silica or colloidal alumina), about 5 wt % to about 40 wt % liquid medium, about 40 wt % to about 85 wt % aluminum oxide powder, optionally about 0.1 wt % to about 10 wt % liquid medium soluble polymer, and optionally a protonic acid to provide a pH of about 3 to about 5 (e.g., about 0.1 wt % to about 2 wt % or about 0.1 wt % to about 1 wt % protonic acid).

[0136] In some embodiments, the slurry mixture completely infiltrates the paper or fabric and is substantially homogeneously or uniformly distributed throughout the paper or fabric. Upon drying, the liquid medium in the slurry is removed from the paper or fabric, leaving a dried slurry infiltrant system that is substantially homogeneously or uniformly distributed throughout the paper or fabric (substantially free of liquid medium (e.g., substantially free of water or alcohol)).

[0137] III. METHODS OF FORMING PREPREG COMPOSITES

[0138] The methods described herein describe various methods of forming surface treated prepreg composites, surface treated layups of prepreg composites with infiltrated paper, in addition to paper and fabric reinforced ceramic matrix composite articles. Each method can include infiltrating an inorganic fabric (such as any inorganic fabric described herein) with a first slurry mixture (such as any slurry mixture described herein) to form an infiltrated fabric. The methods additionally include infiltrating an inorganic paper (such as any inorganic paper described herein) with a second slurry mixture (such as any slurry mixture described herein) to form an infiltrated paper. The methods can additionally include drying the infiltrated fabric and / or the infiltrated paper to form a surface treated prepreg composite, depending on the methodology selected to fabricate the final prepreg composite or ceramic matrix composite article.

[0139] Referring to FIG. 1, a flow diagram is provided illustrating an exemplary method 100 used to form a surface treated fabric reinforced ceramic matrix composite article. The method 100 may begin with infiltrating 104 an inorganic fabric (woven or non-woven) with a first slurry mixture to form an infiltrated fabric. The first slurry mixture may comprise an oxide component, a liquid medium, optionally a liquid medium soluble polymer, and optionally a protonic acid, such as any of the slurry mixtures described herein. The first slurry mixture may be mixed or formed using a high shear mixer, a ball mill, an attritor, a planetary, or any combination thereof. In some aspects, step 104 includes drying the infiltrated fabric to form a prepreg composite.

[0140] Next is infiltrating the inorganic paper with a second slurry mixture to form an infiltrated paper 108. The second slurry mixture may comprise an oxide component, a liquid medium, optionally a liquid medium soluble polymer, and optionally a protonic acid, such as any of the slurry mixtures described herein. The second slurry mixture may be mixed or formed using a high shear mixer, a ball mill, an attritor, a planetary, or any combination thereof. In some aspects, the second slurry mixture may have the same composition as the first slurry mixture. In other aspects, a combination of different slurry mixtures may be used on either the inorganic fabric and / or the inorganic paper. Subsequent applications of the same or different slurry mixtures may be applied when the infiltrated fabric or infiltrated paper is still wet, or alternatively, may be applied to a dried infiltrated paper or fabric-reinforced prepreg composite. In some aspects, step 108 may include drying the infiltrated paper to form a dried or substantially dry infiltrated paper.

[0141] 1 , next is stacking or applying one or more layers of infiltrated paper onto the top and / or bottom surfaces of the fabric reinforced prepreg composite to form a paper / fabric composite (not shown) or an alternating paper / fabric / paper composite or an alternating paper / fabric / paper composite layup 112. In some aspects, the paper / fabric composite or alternating paper / fabric / paper composite is fabricated as the stack is formed by layering the infiltrated paper onto the surface of the infiltrated fabric, each layer still wet from application of the respective first and second slurry mixtures, followed by drying the paper / fabric composite or paper / fabric / paper stack to form a dried paper / fabric composite or alternating paper / fabric / paper composite. Alternatively, in other aspects, a paper / fabric composite or alternating paper / fabric / paper prepreg composite layup is fabricated when a stack is formed by layering fabric-reinforced prepreg composite and infiltrated paper, both types of layers already dried from the drying steps referenced in steps 104 and 108. In some aspects, the fabric-reinforced prepreg composite and infiltrated paper layers can be sticky and layered to form a paper / fabric composite or alternating paper / fabric / paper prepreg composite layup. Now referring to FIG. 2, a cross-sectional schematic of an alternating paper / fabric / paper prepreg composite layup 10 is provided. FIG. 2 illustrates an alternating stack of infiltrated paper 14 on the top and bottom surfaces of a fabric-reinforced prepreg composite 18 to form an alternating paper / fabric / paper composite layup 10.

[0142] In another aspect of FIG. 1, step 116 is layering 116 the fabric prepreg composite with a paper prepreg composite, where at least one layer of the fabric reinforced prepreg composite is stacked alternately with at least one layer of the paper prepreg composite to form a stacked alternating paper / fabric / paper prepreg composite layup. In some aspects, step 116 may alternatively include a stacked alternating paper / fabric / paper prepreg composite that may be fabricated when a stack is formed by layering the infiltrated paper on each side of the infiltrated fabric in a stacked manner (each layer may still be wet from application of the respective first and second slurry mixtures). Subsequent drying of the infiltrated paper / fabric / paper stack can form the alternating paper / fabric / paper prepreg composite. Referring now to FIG. 3 , a cross-sectional schematic of a stacked alternating paper / cloth / paper prepreg composite layup 20 is illustrated having one layer of paper prepreg composite 14 stacked on the top and bottom surfaces of fabric reinforced prepreg composite layup 18 to form the stacked alternating paper / cloth / paper prepreg composite layup 20.

[0143] In yet another aspect of FIG. 1 , next is stacking two or more layers of the fabric reinforced prepreg composite to form a multi-ply fabric reinforced prepreg composite layup 120. In other aspects, step 120 may alternatively include stacking two or more layers of infiltrated fabric followed by drying to form a multi-ply fabric reinforced prepreg composite. Now referring to FIG. 4 , a cross-sectional schematic of a multi-ply fabric reinforced prepreg composite layup 30 is provided. As shown, the stack includes two or more layers of fabric reinforced prepreg composite 18 to form a multi-ply fabric reinforced prepreg composite layup 30. In some aspects, the multi-ply fabric reinforced prepreg composite layup 30 may include four layers of fabric reinforced prepreg composite 18. In other aspects, the multi-ply fabric reinforced prepreg composite layup 30 may include two, three, four, five, six, seven, eight, or more than eight layers of fabric reinforced prepreg composite 18.

[0144] In an additional aspect of FIG. 1, next is stacking one or more layers of paper prepreg composite on the top and bottom surfaces of the multi-ply fabric reinforced prepreg composite layup to form a paper and multi-ply fabric reinforced prepreg composite layup 124. In another aspect, step 124 may include stacking one or more layers of multi-ply infiltrated fabric or infiltrated paper on the top and bottom surfaces of the multi-ply fabric reinforced prepreg composite layup to form a paper and multi-ply fabric reinforced prepreg composite. Now referring to FIG. 5, a cross-sectional schematic of a paper and multi-ply fabric reinforced prepreg composite layup 40 is provided. As shown, one or more layers of paper prepreg composite 14 are stacked on the top and bottom surfaces of the multi-ply fabric reinforced prepreg composite layup 30 to form a paper and multi-ply fabric reinforced prepreg composite layup 40.

[0145] In yet another aspect of FIG. 1 , next is stacking two or more layers of paper prepreg composite to form a multi-ply paper prepreg composite layup 128. In other aspects, step 128 may alternatively include stacking two or more layers of infiltrated paper followed by drying to form a multi-ply paper prepreg composite. Now referring to FIG. 6 , a cross-sectional schematic of a multi-ply paper prepreg composite layup 50 is provided. As shown, two or more layers of paper prepreg composite 18 are stacked to form a multi-ply paper prepreg composite layup 50. In some aspects, the multi-ply paper prepreg composite layup 50 may include four layers of paper prepreg composite 14. In other aspects, the multi-ply paper prepreg composite layup 50 may include two, three, four, five, six, seven, eight, or more than eight layers of paper prepreg composite 18.

[0146] Still referring to FIG. 1, next is to contact or bond 132 at least one of the prepreg composite layups 10, 20, 30, 40, 50 to the surface of the preform. In some aspects, the preform may include, for example, but not limited to, a tool, a panel, a support member, a tank, a screen, a shield, a cable, a wire, a fiber, an inorganic article, an organic article, a layered article, a compounded article, or any combination thereof. In some aspects, the layups illustrated in FIGS. 2-6 may be applied to the preform as respective prepreg composites or prepreg composite layups. In other aspects, the layers provided in FIGS. 2-6 may be applied wet directly to the surface of the preform using respective infiltrated paper and fabric layers, which may be subsequently dried. In some embodiments, at least one of an infiltrated paper, a paper prepreg composite, an infiltrated fabric, a fabric reinforced prepreg composite, an alternating paper / fabric / paper prepreg composite layup, a multi-ply fabric reinforced prepreg composite layup, a paper and a multi-ply fabric reinforced prepreg composite layup, a stacked alternating paper / fabric / paper prepreg composite layup, or any combination thereof, may be contacted or bonded to a surface of a preform to form a matrix article.

[0147] Next is autoclaving, oven curing, and / or press curing the prepregs into the preforms to form a cured matrix article 136. In some aspects, any combination of heat and / or pressure may be used to cure the prepregs and form the cured matrix article, which may generally be referred to as a "curing step." This curing step, e.g., autoclaving, oven curing, and / or press curing, includes applying heat and / or pressure to a fabric reinforced prepreg composite, paper prepreg composite, paper and fabric reinforced stack prepreg composite layup, multi-ply fabric reinforced prepreg composite layup, multi-ply paper and / or fabric reinforced prepreg composite layup to a matrix article to form a cured matrix article. In some aspects, the autoclaving, oven curing, and / or press curing steps are performed at a cure pressure of about 10 psi to about 200 psi, about 70 psi to about 200 psi, or about 10 psi to about 20 psi.

[0148] Next is sintering 140 the cured matrix article to form a fabric reinforced ceramic matrix composite article. In some aspects, the sintering is carried out at a sintering temperature of about 700° C. to about 1,400° C., about 750° C. to about 1,400° C., about 850° C. to about 1,300° C., or about 900° C. to about 1,300° C. In other aspects, the sintering temperature is ramped up to a temperature at a heating rate of about 1° C. / min to about 50° C. / min, about 1° C. / min to about 25° C. / min, or about 1° C. / min to about 10° C. / min.

[0149] It should be understood that the descriptions outlining and teaching the prepreg composites used to form the fabric-reinforced ceramic matrix composite articles discussed above, which may be used in any combination, apply equally well to the method 100 of forming a fabric-reinforced ceramic matrix composite article or prepreg composite.

[0150] The methods of making the reinforced prepreg composites and corresponding structures described herein can provide advantages over currently produced techniques and structures. For example, rather than commonly implemented surface finishing techniques used to coat only the surface or outer portions of the inorganic material, the techniques disclosed herein completely infiltrate the inorganic nonwoven fabric layers, inorganic woven fabric layers, and / or inorganic paper layers to provide homogenous ceramic prepreg composites. The uniform distribution of the slurry mixture throughout the fabric and paper layers provides more uniform material properties in the final manufactured ceramic device. The complete and uniform distribution of the slurry mixture is promoted by both the infiltration conditions, including temperature and pressure, as well as the composition of the slurry, including selecting the appropriate liquid medium.

[0151] The reinforced prepreg composites disclosed herein additionally provide smoother surfaces that may lead to improved airflow across the respective components. These ceramic surfaces can improve surface thermal cycling by minimizing microcracks, thus preventing damage to the surface of the composite part. The techniques used to form these reinforced prepreg composites can improve efficiency in fabrication by reducing production time by shortening the time required to produce a part by minimizing the time required for the polish / fill / polish cycle.

[0152] The fabric reinforced prepreg composites fabricated and disclosed herein can be used for complex tools and / or aeronautical components where both thermal stability and mechanical integrity are important to the ultimate functionality of the respective device. The fabric reinforced prepreg composites disclosed herein demonstrate a number of material properties that make them excellent candidates for applications requiring tough materials that can be used at high temperatures. For example, the fabric reinforced prepreg composites and respective layups used to make the CMCs herein have operating temperatures up to 1,600°C, tensile strengths of at least 50 psi, thicknesses of less than 25 mm, loss on ignition of less than 10%, and heat shrinkage at processing temperatures of less than 6%.

[0153] IV. EXAMPLES

[0154] The following examples are illustrative of the disclosed methods and compositions and are not meant to be limiting. Other suitable modifications and adaptations of the variety of conditions and parameters normally encountered in the art and obvious to those skilled in the art are within the spirit and scope of the disclosure.

[0155] Example 1

[0156] Three inorganic fabrics, namely, DF11-8HS1500D, DF11-5HS3000D, and DF11-TW4500D (3M™ NEXTEL™), were infiltrated with an aqueous aluminum silicate slurry and dried to form prepreg sheets. For the DF11-8HS1500D fabric, the prepreg was cut into 6" x 6" sections and a [0°] 12-ply layup was generated. Two 6" x 6" ALCEN paper swatches (0.3mm thick) were manually prepregged with the aluminum silicate slurry and placed on the top and bottom of the 12-ply layup to form a surface treatment (or surface film). The layup was bagged, autoclave cured at 350°F and 100 psi, and sintered at 2,000°F. 0.5" x 0.2" samples were diamond cut from the laminates and ground to size. The sample was coated with 8 nm of Iridium using an EMS150T sputter coater. Table 1 below provides the material properties obtained for the paper and multi-ply fabric reinforced prepreg composite layup of Example 1. Figures 7-9 are cross-sectional SEM images of the laminate-facing film interface using an FEI Magellan 400 SEM. Figures 10A and 10B are tool side and bag side photographic images, respectively, of the 12 ply prepreg layup of Example 1. The same procedure was used for the DF11-5HS3000D and DF11-TW4500D fabrics.

[0157] [Table 1]

[0158] Paper and multi-ply fabric reinforced prepreg composite layups using three different NEXTEL™ fabrics from Example 1 were tested for their effect on surface and areal roughness when used as a surface treatment or surface film on AX-7810 CMC. The paper and multi-ply fabric reinforced prepreg composite layups from Example 1 that were tested included a paper surface film (or surface treatment) layer. A corresponding sample without a paper surface film layer (or surface treatment) was tested for comparison ("Control"). Surface analysis was performed using a KRUSS Surface Roughness Analyzer (SRA). KRUSS SRA parameters were: itom 3.1.0 software, light intensity 17.6-19%, magnification 10x, measurement area 8.5 x 8 mm, measurement height 350 microns, no roughness cutoff, waviness cutoff 0.8 mm. Surface roughness was determined using confocal microscopy techniques. Line and areal roughness were measured.

[0159] CMC linear roughness values ​​are shown in Surface 2. Ra roughness values ​​are plotted in the graph provided in Figure 11. Use of the composite layup with the paper facing film of Example 1 resulted in significant improvement in linear roughness, i.e., about a 58% reduction in linear roughness for the 8HS1500D and 5HS3000D laminates with facing films, and about a 41% reduction in linear roughness for the TW4500D laminate with facing film, with the facing film roughness values ​​being consistent across all fabric weaves (about 2.7 μm).

[0160] [Table 2]

[0161] CMC surface roughness values ​​are shown in Table 3. Sa roughness values ​​are plotted in the bar graph provided in Figure 12. Use of the composite layup with the paper facing film of Example 1 resulted in significant improvements in surface roughness, i.e., about a 52% reduction in surface roughness for the 8HS1500D laminate, about a 44% reduction in surface roughness for the 5HS3000D laminate, and about a 28% reduction in surface roughness for the TW4500D laminate. Surface roughness decreases in the standard laminates with increasing denier. Surface finish film roughness values ​​were fairly consistent across all fabric weaves (approximately 3.3 μm).

[0162] [Table 3]

[0163] Paper and multi-ply fabric reinforced prepreg composite layups using three different NEXTEL™ fabrics of Example 1 were tested for their effect on dielectric properties when used as a surface film for AX-7810 CMC. The paper and multi-ply fabric reinforced prepreg composite layups of Example 1 that were tested included a paper surface film layer. A corresponding sample without a paper surface film layer was tested for comparison ("Control"). Dielectric testing was performed on a split post dielectric resonator (SPDR) using IEC 61189-2-721, tested at a frequency of 9.5 GHz, a typical DK resolution of <0.1, and a tan delta of 0.00001. For reference, alumina, mullite, and silica have dielectric constants (εr) of 10, 7, and 4, respectively.

[0164] The dielectric properties are shown in Table 4. The dielectric constant (eps') values ​​are plotted in the bar graph provided in Figure 13. The use of the composite layup with the paper facing film of Example 1 resulted in a significant improvement in the dielectric properties, i.e., about a 17% reduction in the dielectric constant, a large reduction in the dielectric constant (believed to be a function of the coupon thickness, standard prepreg ply count, and the dielectric response of the anisotropic matrix-rich facing film perpendicular to the beam).

[0165] [Table 4] (Other embodiments)

[0166] While the present invention has been described in conjunction with the detailed description thereof, it should be understood that the foregoing description is intended to be illustrative, and not limiting, of the scope of the invention, which is defined by the appended claims. Other aspects, advantages, and modifications are within the scope of the following claims.

Claims

1. 1. A method of forming a surface treated fabric reinforced prepreg composite, the method comprising: Providing an inorganic fabric having a thickness of 5 mm to 75 mm; providing an inorganic paper having a thickness of 0.1 mm to 4.99 mm, said inorganic paper being formed from randomly oriented inorganic fibers; infiltrating the inorganic fabric with a first slurry mixture to form an infiltrated fabric, the first slurry mixture comprising an oxide component and a liquid medium; infiltrating the inorganic paper with a second slurry mixture to form an infiltrated paper, the second slurry mixture comprising an oxide component and a liquid medium; and applying the infiltrated paper to a surface of the infiltrated fabric to form a surface treated fabric reinforced prepreg composite; A method comprising:

2. 10. The method of claim 1, further comprising drying the infiltrated fabric prior to applying the infiltrated paper to a surface of the infiltrated fabric.

3. The method of claim 1 further comprising simultaneously drying the infiltrated fabric and the infiltrated paper.

4. The method of any one of claims 1 to 3, wherein the inorganic fabric comprises a plurality of fibers comprising alumina, silica, mullite, zirconia, or any combination thereof.

5. The method of any one of claims 1 to 4, wherein the inorganic fabric is woven, non-woven, or any combination thereof.

6. The method of any one of claims 1 to 5, wherein the inorganic paper comprises alumina, silica, mullite, zirconia, or any combination thereof.

7. 7. The method of any one of claims 1 to 6, wherein the oxide component of the first slurry mixture and / or the second slurry mixture comprises an oxide of one or more of aluminum, silicon, boron, zirconium, yttrium, or any combination thereof.

8. 8. The method of claim 7, wherein the one or more oxides of the first slurry mixture and / or the second slurry mixture are provided as particles comprising spheres, hollow spheres, fibers, whiskers, or any combination thereof.

9. 9. The method of claim 7 or claim 8, wherein the first slurry mixture and / or the second slurry mixture further comprises colloidal silica having an average particle diameter of 1 nanometer to 10 microns.

10. 9. The method of claim 7 or claim 8, wherein the first slurry mixture and / or the second slurry mixture further comprises colloidal alumina having an average particle diameter of 1 nanometer to 10 microns.

11. The method of any one of claims 1 to 10, wherein the liquid medium of the first slurry mixture and / or the second slurry mixture is water, alcohol, or any combination thereof.

12. The first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture, the aqueous slurry mixture comprising: 0.1% to 40% by weight of colloidal silica; 0.1% to 10% by weight of a liquid medium soluble polymer; 40% to 85% by weight of aluminum oxide powder; 10% to 60% by weight of water The method according to any one of claims 1 to 7, comprising:

13. The first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture, the aqueous slurry mixture comprising: 15% to 30% by weight of colloidal silica; 0.1% to 4% by weight of a liquid medium soluble polymer; 45% to 65% by weight of aluminum oxide powder; 20% to 40% by weight of water The method of claim 12, comprising:

14. 14. The method of claim 12 or claim 13, wherein the liquid medium soluble polymer is polyvinyl alcohol.

15. The first slurry mixture and / or the second slurry mixture is an alcohol-based slurry, and the alcohol-based slurry is 0.1% to 50% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; 40% to 85% by weight of aluminum oxide powder; 5% to 60% by weight of alcohol, the alcohol being methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C 5 -C 8 Alcohol, or any combination thereof; The method according to any one of claims 1 to 7, comprising:

16. The first slurry mixture and / or the second slurry mixture is an alcohol-based slurry, and the alcohol-based slurry is 5% to 25% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; 45% to 65% by weight of aluminum oxide powder; 30% to 50% by weight of alcohol, the alcohol being methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C 5 -C 8 Alcohol, or any combination thereof; The method of claim 15, comprising:

17. The method of any one of claims 1 to 16, wherein the pH of the first slurry mixture and / or the second slurry mixture is adjusted to a pH of from 3 to 5 using a protonic acid.

18. The method of any one of claims 1 to 17, wherein the first slurry mixture and / or the second slurry mixture further comprises 0.1% to 2% by weight of a protonic acid.

19. 20. The method of claim 18, wherein the first slurry mixture and / or the second slurry mixture further comprises 0.1% to 1% by weight of a protonic acid.

20. 20. The method of any one of claims 1 to 19, wherein the first slurry mixture and / or the second slurry mixture further comprise one or more additives, the one or more additives comprising an inorganic polymeric material, an organic polymeric material, one or more surfactants, one or more viscosity modifiers, a glycol, a polyol, or any combination thereof.

21. The method of any one of claims 1 to 20, further comprising curing the fabric reinforced prepreg composite at a pressure of 10 psi (6.89 x 104 Pa) to 200 psi (1.3789 x 104 Pa) and a temperature of 75°C to 500°C.

22. The method of claim 21, further comprising sintering the fabric reinforced prepreg composite at a sintering temperature of 700°C to 1400°C.

23. 23. The method of claim 22, wherein the sintering is accomplished using a heating rate of from 1° C. / min to 10° C. / min until the sintering temperature is achieved.

24. 23. The method of any one of claims 1 to 22, further comprising blending the first slurry mixture and / or the second slurry mixture using a high shear mixer, a ball mill, an attritor, a planetary, or any combination thereof.

25. 25. The method according to any one of claims 1 to 24, wherein the inorganic fabric is infiltrated with the first slurry mixture heated to an infiltration temperature of 20°C to 150°C, and / or the inorganic paper is infiltrated with the second slurry mixture heated to an infiltration temperature of 20°C to 150°C.

26. 1. A method of forming a fabric-reinforced ceramic matrix composite article, the method comprising: providing a prepreg composite comprising one or more layers of infiltrated fabric, the infiltrated fabric comprising an inorganic fabric infiltrated with a first slurry mixture comprising an oxide component and a liquid medium; contacting the prepreg composite with a surface of a preform; providing an infiltrated paper having a pre-infiltration thickness of 0.1 mm to 4.99 mm, said infiltrated paper being formed from randomly oriented inorganic fibers, said infiltrated paper comprising an inorganic paper infiltrated with a second slurry mixture comprising an oxide component and a liquid medium; applying the infiltrated paper to at least one surface of the prepreg composite to form a surface treated prepreg composite; sintering the surface treated prepreg composite at a sintering temperature of 700°C to 1400°C to form the fabric reinforced ceramic matrix composite article. A method comprising:

27. 1. A method of forming a fabric-reinforced ceramic matrix composite article, the method comprising: providing a prepreg composite comprising one or more layers of infiltrated fabric, the infiltrated fabric comprising an inorganic fabric infiltrated with a first slurry mixture comprising an oxide component and a liquid medium; contacting the prepreg composite with a surface of a preform; providing an infiltrated paper having a pre-infiltration thickness of 0.1 mm to 4.99 mm, said infiltrated paper being formed from randomly oriented inorganic fibers, said infiltrated paper comprising an inorganic paper infiltrated with a second slurry mixture comprising an oxide component and a liquid medium; applying the infiltrated paper to at least one surface of the prepreg composite to form a surface treated prepreg composite; curing the surface treated prepreg composite at a pressure of 10 psi (6.89×10 4 Pa) to 200 psi (1.3789×10 4 Pa) and a temperature of 75° C. to 500° C.; sintering the surface treated prepreg composite at a sintering temperature of 700°C to 1400°C to form the fabric reinforced ceramic matrix composite article. A method comprising:

28. 1. A method of forming a fabric-reinforced ceramic matrix composite article, the method comprising: providing a prepreg composite comprising one or more layers of infiltrated fabric, the infiltrated fabric comprising an inorganic fabric infiltrated with a first slurry mixture comprising an oxide component and a liquid medium; curing the prepreg composite at a pressure of 10 psi (6.89×10 4 Pa) to 200 psi (1.3789×10 4 Pa) and a temperature of 75° C. to 500° C. to form a cured prepreg composite; providing an infiltrated paper having a pre-infiltration thickness of 0.1 mm to 4.99 mm, said infiltrated paper being formed from randomly oriented inorganic fibers, said infiltrated paper comprising an inorganic paper infiltrated with a second slurry mixture comprising an oxide component and a liquid medium; applying the infiltrated paper to at least one surface of the cured prepreg composite to form a surface treated prepreg composite; sintering the surface treated prepreg composite at a sintering temperature of 700°C to 1400°C to form the fabric reinforced ceramic matrix composite article. A method comprising:

29. The method of any one of claims 26 to 28, wherein the inorganic fabric comprises a plurality of fibers comprising alumina, silica, mullite, zirconia, or any combination thereof.

30. The method of any one of claims 26 to 29, wherein the inorganic fabric has a thickness of from 5 mm to 75 mm before being infiltrated with the first slurry mixture.

31. The method of any one of claims 26 to 30, wherein the inorganic fabric is woven, non-woven, or any combination thereof.

32. The method of any one of claims 26 to 31, wherein the inorganic paper comprises alumina, silica, mullite, zirconia, or any combination thereof.

33. 33. The method of any one of claims 26 to 32, wherein the oxide component of the first slurry mixture and / or the second slurry mixture comprises an oxide of one or more of aluminum, silicon, boron, zirconium, yttrium, or any combination thereof.

34. 34. The method of claim 33, wherein the one or more oxides of the first slurry mixture and / or the second slurry mixture are provided as particles comprising spheres, hollow spheres, fibers, whiskers, or any combination thereof.

35. 35. The method of claim 33 or claim 34, wherein the first slurry mixture and / or the second slurry mixture further comprise colloidal silica having an average particle diameter of 1 nanometer to 10 microns.

36. 35. The method of claim 33 or claim 34, wherein the first slurry mixture and / or the second slurry mixture further comprises colloidal alumina having an average particle diameter of 1 nanometer to 10 microns.

37. The method of any one of claims 26 to 36, wherein the liquid medium of the first slurry mixture and / or the second slurry mixture is water, alcohol, or any combination thereof.

38. The first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture, the aqueous slurry mixture comprising: 0.1% to 40% by weight of colloidal silica; 0.1% to 10% by weight of a liquid medium soluble polymer; 40% to 85% by weight of aluminum oxide powder; 10% to 60% by weight of water The method according to any one of claims 26 to 33, comprising:

39. The first slurry mixture and / or the second slurry mixture is an aqueous slurry mixture, the aqueous slurry mixture comprising: 15% to 30% by weight of colloidal silica; 0.1% to 4% by weight of a liquid medium soluble polymer; 45% to 65% by weight of aluminum oxide powder; 20% to 40% by weight of water 39. The method of claim 38, comprising:

40. 40. The method of claim 38 or claim 39, wherein the liquid medium soluble polymer is polyvinyl alcohol.

41. The first slurry mixture and / or the second slurry mixture is an alcohol-based slurry, and the alcohol-based slurry is 0.1% to 50% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; 40% to 85% by weight of aluminum oxide powder; 5% to 60% by weight of alcohol, the alcohol being methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C 5 -C 8 Alcohol, or any combination thereof; The method according to any one of claims 26 to 33, comprising:

42. The first slurry mixture and / or the second slurry mixture is an alcohol-based slurry, and the alcohol-based slurry is 5% to 25% by weight of one or more organic binders, the organic binder comprising a silicone resin, polyvinyl butyral, polyvinyl acetate, polylactic acid, or any combination thereof; 45% to 65% by weight of aluminum oxide powder; 30% to 50% by weight of alcohol, the alcohol being methanol, ethanol, n-propanol, isopropanol, n-butanol, t-butanol, sec-butanol, C 5 -C 8 Alcohol, or any combination thereof; The method according to any one of claims 26 to 33, comprising:

43. The method of any one of claims 26 to 33, wherein the pH of the first slurry mixture and / or the second slurry mixture is adjusted to a pH of from 3 to 5 using a protonic acid.

44. The method of any one of claims 26 to 33, wherein the first slurry mixture and / or the second slurry mixture further comprises 0.1% to 2% by weight of a protonic acid.

45. 45. The method of claim 44, wherein the first slurry mixture and / or the second slurry mixture further comprises 0.1% to 1% by weight of a protonic acid.

46. 46. ​​The method of any one of claims 26 to 45, wherein the first slurry mixture and / or the second slurry mixture further comprise one or more additives, the one or more additives comprising an inorganic polymeric material, an organic polymeric material, one or more surfactants, one or more viscosity modifiers, a glycol, a polyol, or any combination thereof.

47. A method according to any one of claims 26 to 46, wherein the sintering is carried out using a heating rate of from 1°C / min to 10°C / min until the sintering temperature is achieved.

48. A surface-treated prepreg composite, the surface-treated prepreg composite comprising: an infiltrated fabric having a top layer and a bottom layer, said infiltrated fabric having a pre-infiltration thickness of 5 mm to 75 mm, said infiltrated fabric comprising fibers comprising alumina, silica, mullite, or any combination thereof, said top layer and said bottom layer forming a coating on said infiltrated fabric, each surface layer comprising 40% to 85% by weight (by weight of said surface layer) aluminum oxide or 0.1% to 40% by weight (by weight of said surface layer); an infiltrated paper having a pre-infiltration thickness of 0.1 mm to 4.99 mm, said infiltrated paper being formed from randomly oriented inorganic fibers, said infiltrated paper substantially covering and in contact with a top layer and / or a bottom layer of said infiltrated fabric, said infiltrated paper comprising fibers comprising alumina, silica, mullite, or any combination thereof, said infiltrated paper being infiltrated with a slurry mixture comprising an oxide component and a liquid medium; A surface treated prepreg composite comprising:

49. A surface-treated prepreg composite, the surface-treated prepreg composite comprising: a plurality of infiltrated fabric layers, each infiltrated fabric layer having a pre-infiltration thickness of 5 mm to 75 mm, said layers stacked in contact with one another to form a multi-ply fabric reinforced prepreg composite lay-up, said prepreg composite lay-up having a top surface and a bottom surface, each of said infiltrated fabric layers comprising fibers comprising alumina, silica, mullite, or any combination thereof, said fibers being at least partially coated with said coating comprising 40% to 85% by weight (by weight of said coating) aluminum oxide or 0.1% to 40% by weight silica (by weight of said coating); an infiltrated paper having a pre-infiltration thickness of 0.1 mm to 4.99 mm, said infiltrated paper being formed from randomly oriented inorganic fibers, said infiltrated paper covering at least a portion of said top surface and / or said bottom surface of said prepreg composite lay-up, said infiltrated paper comprising fibers comprising alumina, silica, mullite, or any combination thereof, said infiltrated paper being infiltrated with a slurry mixture comprising 40% to 85% by weight (by weight of the slurry) aluminum oxide or 0.1% to 40% by weight silica (by weight of the slurry); A surface treated prepreg composite comprising:

Citation Information

Patent Citations

  • Multilayer coating system containing thiol-functional compounds

    JP2005535450A

  • Method of manufacturing a ceramic matrix composite article

    US20110259506A1

  • Damage tolerant CMC using sol-GEL matrix slurry

    WO2002085618A1